Functional characterization of two corticotropin-releasing hormone receptors in Larimichthys crocea - Liu, Xue; Feng, Jiaqian; Jiang, Zhijing; Zhang, Guangbo; Xu, Xiuwen; Wang, Jixiu; Yang, Jingwen; Wang, Tianming (Frontiers in Marine Science, 2023)
In the neuroendocrine system, corticotropin-releasing hormone (CRH) plays an important role in the hypothalamic–pituitary–adrenal/interrenal (HPA/HPI) axis. It exerts its effects by activating CRHRs, which belong to the class B G protein-coupled receptor family. Two characteristic genes of CRHR1 subtypes in the Larimichthys crocea genome were identified: LcCRHR1-1 and LcCRHR1-2. Alignments indicated that they were highly homologous to known and validated teleost CRHR1s. The CDS sequences of the two receptors were cloned into the pEGFP-N1 plasmid, and membrane localization of the fusion expressing LcCRHR1-1-EGFP and LcCRHR1-2-EGFP was revealed in HEK293 cells. Treatment with LcCRH could lead to two receptors internalization and trigger a significant increase in the levels of the secondary messenger cAMP and Ca2+ and mitogen-activated protein kinase phosphorylation in an LcCRH dose-dependent manner. Based on quantitative real-time PCR, LcCRHR1s were expressed in all examined tissues and highly expressed in the brain and ovaries. Furthermore, immunohistochemical findings showed the specific localization of CRHR1s in ovarian follicle cells. Collectively, our study identified two CRH receptors in L. crocea and suggested that the CRH/CRHR1 system is potentially involved in the neuroendocrine regulation of reproduction in this marine fish.